2020
DOI: 10.1093/jjco/hyaa100
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle measurements predict surgical wound complications but not overall survival in patients with soft tissue sarcoma

Abstract: Background It is unknown whether sarcopenia influences treatment outcome in patients with soft tissue sarcoma. Herein, we aimed to elucidate the impact of sarcopenia on sarcoma treatment. Methods A total of 163 soft tissue sarcoma patients were included. Skeletal muscle measures were calculated using computed tomography images. Skeletal muscle area (SMA) and density (SMD) at the L3 level were extracted, and SMA was normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…These previous studies investigated the clinical significance of SMG in female patients with cancer; the studies had relatively small sample sizes; thus, comparison of the mean or median SMG values between the sexes has been scarcely reported. Hirai et al reported that the mean SMG value was higher in men than in women (1729 AU vs. 1343 AU, p < 0.0001) who underwent surgeries for soft tissue sarcoma 28 . Consistent with this result, our cohort showed a higher median SMG value in the male patients than in the female patients both in the training and test sets.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These previous studies investigated the clinical significance of SMG in female patients with cancer; the studies had relatively small sample sizes; thus, comparison of the mean or median SMG values between the sexes has been scarcely reported. Hirai et al reported that the mean SMG value was higher in men than in women (1729 AU vs. 1343 AU, p < 0.0001) who underwent surgeries for soft tissue sarcoma 28 . Consistent with this result, our cohort showed a higher median SMG value in the male patients than in the female patients both in the training and test sets.…”
Section: Discussionsupporting
confidence: 89%
“…Hirai et al reported that the mean SMG value was higher in men than in women (1729 AU vs. 1343 AU, p < 0.0001) who underwent surgeries for soft tissue sarcoma. 28 Consistent with this result, our cohort showed a higher median SMG value in the male patients than in the female patients both in the training and test sets. Thus, we decided to define sex-specific cutoff SMG values and confirmed that this newly developed stratification could be used as a significant prognostic factor even in an independent cohort.…”
Section: Discussionsupporting
confidence: 87%
“…First, statistical calculation of the cut-offs was different: cut-offs were calculated either as mean-2 SD [8], median [9], a percentile [10][11][12] or as a predictor for a cut-off of another imaging method (dual-energy X-ray absorptiometry (DXA) [13]), as a predictor for wound complication [14], likelihood of tumour resection [15], mortality [3] or length of stay [16]. Second, adjustment of the cut-offs was different: sometimes, SMA was nonadjusted and expressed in cm 2 [6,8].…”
Section: Introductionmentioning
confidence: 99%